If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(z + -12) = 3(2z + 4) Reorder the terms: 8(-12 + z) = 3(2z + 4) (-12 * 8 + z * 8) = 3(2z + 4) (-96 + 8z) = 3(2z + 4) Reorder the terms: -96 + 8z = 3(4 + 2z) -96 + 8z = (4 * 3 + 2z * 3) -96 + 8z = (12 + 6z) Solving -96 + 8z = 12 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. -96 + 8z + -6z = 12 + 6z + -6z Combine like terms: 8z + -6z = 2z -96 + 2z = 12 + 6z + -6z Combine like terms: 6z + -6z = 0 -96 + 2z = 12 + 0 -96 + 2z = 12 Add '96' to each side of the equation. -96 + 96 + 2z = 12 + 96 Combine like terms: -96 + 96 = 0 0 + 2z = 12 + 96 2z = 12 + 96 Combine like terms: 12 + 96 = 108 2z = 108 Divide each side by '2'. z = 54 Simplifying z = 54
| r^2+6rg-16g^2= | | 14-z=8 | | W-4= | | x + 14 x = 10 | | 40,000*90,000,000= | | 11/(12-8*3)+4 | | b^2+3b+88= | | v=3.14rh^2 | | 12x-19=2x+1 | | -9=-6y+3(y-8) | | 7.1+5-6.1=6 | | 3x-5i=xi | | 3(2x+1)=31/3 | | 63/-3 | | 440/60= | | 2+3ln(2x)=20 | | 7x+9=59+2x | | z+12z-48=0 | | 3n+14-2n=18 | | 2f+4s=5.9 | | 6x^2+1.5x-13.5=0 | | -6x+8=-10 | | a^2-a-20= | | 5x+7=x-4 | | 176=(15-2x)(12-2x)x | | 6x^2+1.5-13.5=0 | | 4(6x-33)=72 | | y=-(1/32)(x+1)^2+4 | | 192*5/8 | | 33=((2x)^2)/((0.06-x)(0.03-x)) | | 5a+16=51 | | (6x-36)=9 |